Fragment o dimenzijah emocije, "mathesisa" in časa v čisto glasbenem - Popović Mlađenović, Tijana (Muzikološki zbornik, 2007)
In the dialogue What Is Music? between Carl Dahlhaus and Hans Heinrich Eggebrecht, music is defined as a "mathematized emotion" or an "emotionalized 'mathesis'". As emphasized by Marija Bergamo, this is the way of underlining its equal and unavoidable constitution, based on emotion and rational organization in the time dimension. So, Marija Bergamo is continuously searching for those music determinants in a musical work as an "autonomous aesthetic fact", whose base and real essence lie "within the nature and essence of music itself". In other words, the starting point of the author's concern with (art) music is her reflection on that which is "purely musical", that is, on "the very nature of the musical". The attempts to determine what the purely musical is and to understand the nature of the sense and inevitability of man's musical dimension have been made since the beginnings of music and musical thinking. In that context, more recent knowledge and thinking about the phenomenon of music, which are derived from various disciplines, correspond closely to Marija Bergamo's views. In a narrower sense, the notion of purely musical is closely related to aesthetic autonomy, that is, autonomous music or musical autonomy. From such a viewpoint - and in conformity with Marija Bergamo's view - I would say that the purely musical in an art music work exists independently of non/autonomy (that is, independently of any function, except an aesthetic one), as well as independently of the origin of its content (musical or extra-musical), and that it always, whenever "one thinks in the sense of music and is seized by it" (in terms of emotion, mathesis and time), creates, brings and possesses its specific (nonconceptual perceptive) musical-semantic stratum. This is shown, at least partly, on a characteristic and (in many respects) paradigmatic example - the music of Prelude to the Afternoon of a Faun by Claude Debussy. Therefore, rationalism of the magic inspiration of music (and/or: in music; by music; and possibly /by music/ about music), as a "mathematized emotion" or "emotionalized mathesis" in the time dimension, makes it - in a purely musical sense, based on purely musical logic - a unique form of non-conceptual cognition.
Keywords: čisto glasbeno; filozofija glasbe; glasba; mathesis; music